The Interplay of Climate Change, Urbanisation, and Species Traits Shapes European Butterfly Population Trends - Pau Colom; Ashley Tejeda; Simona Bonelli; Benoît Fontaine; Mikko Kuussaari; Dirk Maes; Xavier Mestdagh; Miguel L. Munguira; Martin Musche; Lars B. Pettersson; David Roy; Johannes Rüdisser; et al. (Global Ecology and Biogeography, 2026)
Aim To examine how butterfly population trends respond to climate change and urbanisation at a continental scale, and whether responses differ between urban and rural environments. Location 869 sites across 12 European countries, spanning six bioclimatic zones. Time Period 1976–2021. Major Taxa Studied Butterflies (Lepidoptera). Methods We analysed long‐term monitoring data from > 8400 populations of 145 species representing a wide range of ecological and life‐history traits. Population trends were modelled in relation to climate variables (temperature, precipitation and aridity), urbanisation (built‐up surface), and their interactions with urban context (urban vs. rural) and species traits (trophic specialisation, body size, reproductive rate and thermal adaptation). Results Climate warming and aridification were consistently linked to population declines in both rural and urban contexts, while precipitation effects varied by location and species. Urbanisation alone did not predict trends, but the urban–rural context strongly modulated species' responses to warming, indicating potential synergies between climate change and urbanisation. The stronger impact of warming in urban populations likely reflects elevated baseline temperatures and reduced habitat suitability and connectivity in urban landscapes, limiting thermal buffering. Species with colder thermal niches and lower reproductive rates were most vulnerable to warming, as warming exceeds the thermal optima of cold‐adapted species and lower reproductive rates limit their capacity to buffer climate‐driven population declines. Under aridification, which can reduce host‐plant availability, trophic specialists declined more in urban areas, whereas generalists unexpectedly declined more in rural sites, suggesting context‐dependent constraints under increasing water limitation. Main Conclusions Our findings highlight the complex interplay between climate change, urban context, and species traits in driving population dynamics. Importantly, our results suggest that urbanisation generally amplifies the negative impact of climate change on insect population trends.

Assessing landscape-level effects of permanent grassland management and landscape configuration on open-land butterflies based on national monitoring data - Toni Kasiske; Jens Dauber; Petra Dieker; Alexander Harpke; Sebastian Klimek; Elisabeth Kühn; Christian Levers; Marcel Schwieder; Josef Settele; Martin Musche (Biodiversity and Conservation, 2024)
Halting and reversing the ongoing insect decline requires in-depth knowledge on key drivers. Due to their sensitivity to habitat quality, butterflies are valuable indicators for grassland management intensity, including mowing. However, most studies examining mowing regime impacts on butterflies are limited to small spatial extents. Here, we tested the potential of citizen science butterfly monitoring data for assessing landscape-level effects of mowing regimes (number of mowing events and timing of the first event) and edge density (density of boundaries between different land-cover types) on butterfly richness, abundance, and community composition. We used generalised linear mixed-effects models to relate nationwide data from the German Butterfly Monitoring Scheme (DEBMS) to high-resolution satellite imagery on mowing events in permanent grasslands (grasslands excluded from crop rotation). As butterfly transects may not consistently be located within grasslands, we ran our models for different thresholds from 0 to 50%, representing increasing shares of the transect route situated within permanent grasslands (10% intervals). We did not find significant associations between mowing regimes and butterflies when focussing on species richness and abundance of all species inhabiting open land. However, we found strong positive associations of delayed mowing with the abundance of grassland specialists with increasing grassland shares per transect. Further, we found negative associations of delayed mowing with the annual number of generations and of more frequent mowing with the abundance of specialists, depending on the share of grassland per transect. Edge density had a positive association with species richness and abundance of species inhabiting open land, as well as abundance of grassland indicator species and grassland specialists in landscapes with a low grassland share per transect. Our findings underscore the importance of low-intensity managed permanent grasslands at the landscape scale for specialised butterflies. Additionally, we highlight the importance of a high density of boundaries for open-land and specialised butterflies, particularly in landscapes with highly fragmented permanent grasslands. To improve future analyses of grassland management impacts, we recommend expanding DEBMS monitoring sites to cover a larger grassland management intensity gradient and to place more transects within grasslands.

European butterfly populations vary in sensitivity to weather across their geographical ranges - Simon C. Mills; Tom H. Oliver; Richard B. Bradbury; Richard D. Gregory; Tom Brereton; Elisabeth Kühn; Mikko Kuussaari; Martin Musche; David B. Roy; Reto Schmucki; Constantí Stefanescu; Chris van Swaay; et al. (Global Ecology and Biogeography, 2017)
Aim The aim was to assess the sensitivity of butterfly population dynamics to variation in weather conditions across their geographical ranges, relative to sensitivity to density dependence, and determine whether sensitivity is greater towards latitudinal range margins. Location Europe. Time period 1980–2014. Major taxa studied Butterflies. Methods We use long‐term (35 years) butterfly monitoring data from > 900 sites, ranging from Finland to Spain, grouping sites into 2° latitudinal bands. For 12 univoltine butterfly species with sufficient data from at least four bands, we construct population growth rate models that include density dependence, temperature and precipitation during distinct life‐cycle periods, defined to accommodate regional variation in phenology. We use partial R 2 values as indicators of butterfly population dynamics' sensitivity to weather and density dependence, and assess how these vary with latitudinal position within a species' distribution. Results Population growth rates appear uniformly sensitive to density dependence across species' geographical distributions, and sensitivity to density dependence is typically greater than sensitivity to weather. Sensitivity to weather is greatest towards range edges, with symmetry in northern and southern parts of the range. This pattern is not driven by variation in the magnitude of weather variability across the range, topographic heterogeneity, latitudinal range extent or phylogeny. Significant weather variables in population growth rate models appear evenly distributed across the life cycle and across temperature and precipitation, with substantial intraspecific variation across the geographical ranges in the associations between population dynamics and specific weather variables. Main conclusions Range‐edge populations appear more sensitive to changes in weather than those nearer the centre of species' distributions, but density dependence does not exhibit this pattern. Precipitation is as important as temperature in driving butterfly population dynamics. Intraspecific variation in the form and strength of sensitivity to weather suggests that there may be important geographical variation in populations' responses to climate change.

Research needs for incorporating the ecosystem service approach into EU biodiversity conservation policy - Christian Anton; Juliette Young; Paula A. Harrison; Martin Musche; Györgyi Bela; Christian K. Feld; Richard Harrington; John R. Haslett; György Pataki; Mark D. A. Rounsevell; Michalis Skourtos; J. Paulo Sousa; et al. (Biodiversity and Conservation, 2010)

Myrmica host-ants limit the density of the ant-predatory large blue Maculinea nausithous - Christian Anton; Martin Musche; Vladimir Hula; Josef Settele (Journal of Insect Conservation, 2008)

Population structure of a large blue butterfly and its specialist parasitoid in a fragmented landscape - CHRISTIAN ANTON; INGA ZEISSET; MARTIN MUSCHE; WALTER DURKA; JACOBUS J. BOOMSMA; JOSEF SETTELE (Molecular Ecology, 2007)
Habitat fragmentation may interrupt trophic interactions if herbivores and their specific parasitoids respond differently to decreasing connectivity of populations. Theoretical models predict that species at higher trophic levels are more negatively affected by isolation than lower trophic level species. By combining ecological data with genetic information from microsatellite markers we tested this hypothesis on the butterfly Maculinea nausithous and its specialist hymenopteran parasitoid Neotypus melanocephalus . We assessed the susceptibility of both species to habitat fragmentation by measuring population density, rate of parasitism, overall genetic differentiation (θ ST ) and allelic richness in a large metapopulation. We also simulated the dynamics of genetic differentiation among local populations to asses the relative effects of migration rate, population size, and haplodiploid (parasitoid) and diploid (host) inheritance on metapopulation persistence. We show that parasitism by N. melanocephalus is less frequent at larger distances to the nearest neighbouring population of M. nausithous hosts, but that host density itself is not affected by isolation. Allelic richness was independent of isolation, but the mean genetic differentiation among local parasitoid populations increased with the distance between these populations. Overall, genetic differentiation in the parasitoid wasp was much greater than in the butterfly host and our simulations indicate that this difference is due to a combination of haplodiploidy and small local population sizes. Our results thus support the hypothesis that Neotypus parasitoid wasps are more sensitive to habitat fragmentation than their Maculinea butterfly hosts.